Culturally Contextualized E-Module Based on Papua: Why Teachers and Students Need It for Teaching Linear Programming Material? - Karunia Tumba Sanda Pakabu; Sudirman Sudirman; Thesa Kandaga (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
The use of e-modules in mathematics learning significantly aids both teachers and students in the teaching and learning process. However, the design of e-modules has not been extensively linked to the cultural context in which students live. Therefore, this study aims to explore and analyze the needs of teachers and students in developing culturally integrated e-modules, particularly those reflecting the culture of Papua, for high school students. The research design employed is phenomenological. Participants included Mathematics teachers for grades X, XI, and XII in Nduga Regency, Papua Highlands, and 64 high school students (42 male and 22 female). Data collected from observations and interviews were qualitatively analyzed using Miles-Huberman Interactive Analysis. Findings revealed that the high schools still use the 2013 curriculum, relying on standard textbooks as teaching materials. These textbooks pose problems for students as they are often uninteresting, use formal language, are difficult to understand due to abstract content, and are not contextualized to students' daily lives. Additionally, the reduction in face-to-face learning hours, due to the school's location in a conflict area, hampers effective teaching and learning processes. Another interesting finding is that high schools in Nduga Regency have not yet utilized technology in learning, despite having internet access. These findings imply the need for teaching materials integrated with technology and local culture to help students understand mathematics concepts and assist teachers in teaching both inside and outside the school.